Post-Prostatectomy Image-Guided Radiotherapy: The Invisible Target Concept - Vilotte, Florent; Antoine, Mickael; Bobin, Maxime; Latorzeff, Igor; Supiot, Stéphane; Richaud, Pierre; Thomas, Laurence; Leduc, Nicolas; Guérif, Stephane; Iriondo-Alberdi, Jone; de Crevoisier, Renaud; Sargos, Paul (Frontiers in Oncology, 2017)
In the era of intensity modulated radiation therapy, image guided radiotherapy (IGRT) appears crucial to control dose delivery and to promote dose escalation while allowing healthy tissue sparing. The place of IGRT following radical prostatectomy is poorly described in the literature. This review aims to highlight some key-points on the different IGRT techniques applicable to prostatic bed radiotherapy. Furthermore, methods used to evaluate target motion and to reduce planning target volume margins will also be explored.